KINEMATIC AND DYNAMIC ASPECTS OF THE MANDIBULAR BIOMECHANICS THAT ARE THE BASIS OF THE DESIGN OF A SIM - Gabriel G. Condurache; Kamel Earar; Madalina Matei; Costel Iulian Mocanu (Romanian Society of Oral Rehabilitation, 2022)
In the functional dynamics of the mandible, only hinge and propulsion movements are encountered as pure movements, the other types of movements being included in the combined movements that the mandible performs. From this wide range of movements, the individual will subconsciously choose those that allow mastication as easy as possible, with maximum efficiency with as little stress as possible on the masticatory muscles and periodontal tissues. The stereotype is established on the basis of morphological peculiarities at the level of the temporomandibular joints, jaws and dental arches, aimed at the shape of the mandibular condyles and the inclination of the slope of the articular tubercles, the general shape of the mandible and the opening of the mandibular angle, the dental-dental relationships that are created over time, the masticatory muscles. For the simulator operating, the tribological parameters testing facility specific to the biomaterials used in hip endoprosthesis was adapted, using the cam-spring-tachet loading system, but with the spring replaced.